Distribution of caffeine levels in urine in different sports in relation to doping control before and after the removal of caffeine from the WADA doping list - van Thuyne, W.; Delbeke, F. T. (International Journal of Sports Medicine, 2006)
Caffeine concentrations were measured in the urine of 4633 athletes tested for doping control in the Ghent Doping Control Laboratory in 2004. Determination of these concentrations was done using an alkaline extraction with a mixture of dichloromethane and methanol (9 : 1; v/v) followed by high performance liquid chromatography and ultraviolet detection (HPLC-UV). The method was validated according to ISO 17 025 standards (International Organisation for Standardisation). Quantification was done by using a linear calibration curve in the range from 0 to 20 µg/ml. The limit of quantification (LOQ) was 0.10 µg/ml. Because the results were not normally distributed, transformation of the data was done to evaluate the difference in detected concentrations in several sports. This resulted in an overall average concentration of 1.12 ± 2.68 µg/ml. Comparison of the most frequently tested sports in 2004 demonstrated that caffeine concentrations in samples originating from power lifters are significantly higher in comparison to urines taken in other sports. Also, a significant difference between caffeine concentrations found in cycling and concentrations found in other sports, including athletics and some ball sports, was observed. A comparison was made between results obtained in 2004 and results obtained before the removal of caffeine from the WADA (World Anti-Doping Agency) doping list indicating that average caffeine concentrations decreased after the withdrawal of caffeine from the list of prohibited substances. The overall percentage of positive samples between the two periods remained the same although the percentage of positive samples noticed in cycling increased after the removal of caffeine from the doping list.